2021
DOI: 10.3389/fimmu.2021.749659
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Potential of Mesenchymal Stromal Cell-Derived Extracellular Vesicles in the Prevention of Organ Injuries Induced by Traumatic Hemorrhagic Shock

Abstract: Severe trauma is the principal cause of death among young people worldwide. Hemorrhagic shock is the leading cause of death after severe trauma. Traumatic hemorrhagic shock (THS) is a complex phenomenon associating an absolute hypovolemia secondary to a sudden and significant extravascular blood loss, tissue injury, and, eventually, hypoxemia. These phenomena are responsible of secondary injuries such as coagulopathy, endotheliopathy, microcirculation failure, inflammation, and immune activation. Collectively,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 315 publications
(404 reference statements)
1
12
0
Order By: Relevance
“…MSCs are multipotent stem cells, which are commonly used as a clinical cell therapeutic strategy for immunomodulation and tissue repair ( 9 , 56 ). Treg cells, an immunosuppressive T cell subset, are essential for maintaining immune homeostasis and tolerance ( 57 ).…”
Section: New Insights Into Hs Therapeutics With Innate Immune Regulationmentioning
confidence: 99%
See 3 more Smart Citations
“…MSCs are multipotent stem cells, which are commonly used as a clinical cell therapeutic strategy for immunomodulation and tissue repair ( 9 , 56 ). Treg cells, an immunosuppressive T cell subset, are essential for maintaining immune homeostasis and tolerance ( 57 ).…”
Section: New Insights Into Hs Therapeutics With Innate Immune Regulationmentioning
confidence: 99%
“…In a rat model of unilateral lung contusion followed by HS, impaired wound healing and lung structure were improved by MSCs treatment by increasing the Treg cell population ( 44 , 45 ). Cell-based therapies using MSCs or MSC-EVs are beneficial for improving neurologic outcomes and lung injury in animal models of HS ( 9 ). Moreover, in an HS-induced mild lung injury rat model, leukocyte infiltrates (CD68 + and MPO + cells) were significantly reduced in the lung after treatment with MSCs ( 46 ).…”
Section: New Insights Into Hs Therapeutics With Innate Immune Regulationmentioning
confidence: 99%
See 2 more Smart Citations
“…Extracellular vesicles (EVs), a lipid membranous vesicle, can alter the effects of recipient cells through the transport of a variety of lipids, proteins, DNAs, and RNAs and thus function to cellular processes (12). An existing study reported that EVs derived from mesenchymal stromal cells can protect injured organs from traumatic hemorrhagic shock through limiting apoptosis, inflammation, and oxidative stress (13). It is noteworthy that EVs derived from multiple cells, such as fibrous cells and mesenchymal stem cells, could affect IVD degeneration (14,15).…”
Section: Introductionmentioning
confidence: 99%